2012
DOI: 10.4172/2155-952x.1000139
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Silk-elastin-like Protein Suppresses Cells Adhesion without Apoptosis

Abstract: The objective of this study is to evaluate the effect of an artificial silk-elastin-like protein (SELP) on the adhesion and apoptotic behavior of cells. When MC3T3-E1 cells were cultured on dishes coated with different concentrations of SELP, the cells adhesion was suppressed with the increasing coating concentration. As controls, the coating with fibronectin enhanced the number of cells adhered in the concentration dependent manner. The poly (vinyl alcohol) (PVA) and agarose coating suppressed the cell adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This SELP nature of self-gelation is useful as the material of wound covering. SELP showed a property to suppress cells’ adhesion without their apoptosis . The SELP has good biocompatibility which was experimentally confirmed by an intradermal injection to a guinea pig .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This SELP nature of self-gelation is useful as the material of wound covering. SELP showed a property to suppress cells’ adhesion without their apoptosis . The SELP has good biocompatibility which was experimentally confirmed by an intradermal injection to a guinea pig .…”
Section: Introductionmentioning
confidence: 80%
“…SELP showed a property to suppress cells' adhesion without their apoptosis. 25 The SELP has good biocompatibility which was experimentally confirmed by an intradermal injection to a guinea pig. 22 SELP promotes the in vitro migration, proliferation, and proteins' production of fibroblasts, as well as the migration of macrophages.…”
Section: ■ Introductionmentioning
confidence: 90%
“…Considering its effects on fibroblasts, Somamoto et al. reported that SE inhibits the adhesion of fibroblasts without apoptosis in vitro [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the SELP suppresses the apoptosis of cells. 25 In addition, nanoparticles and hydrogels prepared from SELP are applied to the delivery material of growth factors and plasmid DNA. 74 Based on the findings, we can say that SELP is a promising biomaterial and may have a potential to modify the inflammation response.…”
Section: Discussionmentioning
confidence: 99%
“…SELP showed a property to suppress cell adhesion without their apoptosis. 25 The SELP has good biocompatibility which was experimentally confirmed by the intradermal injection into guinea pig. 22 SELP promotes the in vitro migration, proliferation, and proteins production of fibroblasts, as well as the migration of macrophages.…”
Section: Introductionmentioning
confidence: 90%